Efficacy and safety of reduced thromboprophylaxis with low molecular weight heparin for hepatocellular carcinoma after conversion therapy - Xu Zhang; Zhiguo Ai (BMC Gastroenterology)
Abstract Background Tyrosine kinase inhibitors (TKIs) impairs factor Xa (FXa)-mediated coagulation. This study aims to assess the safety and feasibility of reduced thromboprophylaxis with low molecular weight heparin (LMWH) for hepatocellular carcinoma (HCC) converted by Lenvatinib treatment. Methods One hundred forty consecutive HCC patients who received Lenvatinib standalone therapy before hepatectomy were retrospectively enrolled. Group A received reduced LMWH (≤ 100 IU/kg daily for ≤ 5 days), while Group B received no pharmacologic thromboprophylaxis. Primary outcome was incidence of thrombotic or hemorrhagic complications. Secondary outcome was overall survival (OS). Results Sixty-two and seventy-four patients were divided into group A and B respectively. The incidence of VTE (4.8% vs. 14.9%, P = 0.091, OR = 0.31, 95% CI: 0.08–1.16) and postoperative hemorrhage (3.2% vs. 9.5%, P = 0.298, OR = 0.34, 95% CI: 0.07–1.69) trended lower in Group A. Conclusion Limitations include a retrospective design, potential selection bias, and limited statistical power. Our findings suggest a trend toward reduced hemorrhagic and thrombotic risks with reduced LMWH, though statistical significance was not reached (VTE P = 0.091, hemorrhage P = 0.298) reduce such risks in HCC patients after neoadjuvant Lenvatinib and hepatectomy, though limitations like the retrospective design should be noted. Clinically, reduced LMWH prophylaxis offers a safe alternative for high-bleeding-risk patients, guiding surgical teams to balance thrombosis-bleeding risks and informing oncologists’ perioperative anticoagulation strategies. Trial registration Not applicable.